Ocean's twelve [videorecording (DVD)] - Soderbergh, Steven, 1963-; Clooney, George; Pitt, Brad, 1963-; Damon, Matt; Zeta-Jones, Catherine, 1969-; Garcia, Andy; Cheadle, Don; Mac, Bernie; Roberts, Julia, 1967- (Warner Home Video, 2005)
Ocean's Twelve reintroduces Ocean and his perfectly trained team of con men. Dividing forces to hit Paris, Amsterdam, and Rome, the heist-meisters move beyond casinos to tackle new objectives, one of which involves stealing a famous painting.